Toward a Bank Shareholder-Orientated Model: Using Double Liability to Mitigate Excessive Risk-Taking - Richard Ridyard (UCL Journal of Law and Jurisprudence, 2015)
The conventional model for corporate governance depends on the rarely articulated assumption that the costs of failure are largely internalised by the firm and so are taken into account when shareholders determine their risk appetite. In this paper I argue that, when applied to banks, this view is mistaken. Banks do not internalise the costs of failure, hence the risk appetite of bank shareholders is socially excessive. I show that shareholder pressure on their management to accept greater risk can help explain the excessive risk-taking of banks. My analysis indicates that recent corporate governance reforms that attempt to tighten the alignment of managerial and shareholder interests cannot be expected to address the problem I identify. To adequately understand what policies should be explored, we must first recognise that excessive risk-taking is also partly a product of the conventional model. I therefore propose a modification to the conventional model: a regime of double liability that is triggered by bank failure. I analyse how this will reduce bank shareholders’ risk appetite and make excessive risk-taking less likely. Welfare improvement occurs because of heightened risk awareness and enhanced risk-taking controls, decreasing the likelihood of failure. Finally, examining a range of possible objections, I conclude that they do not provide a good basis for opposing a regime of double liability and the burden is now on proponents to justify the current limited liability regime for bank shareholders. Read more